Operational Curriculum Development : Best Practice in State Junior High School 1 Mantup Indonesia - Supriyanto, Supriyanto; Wulandari, Ayu; Hariyati, Nunuk; Khamidi, Amrozi (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to describe the development of operational curriculum at State Junior High School 1 Mantup. Methods: This research is a type of qualitative research with a case study approach. Presenting descriptive data with interview, observation and documentation methods. Results: The result of this study is that State Junior High School 1 Mantup adds local content in accordance with the Governor's regulation and the Lamongan Regent Regulation. The local content is Javanese and Arabic which must be included in the curriculum structure. The project of strengthening the student profile of Pancasila as a compulsory subject also takes themes that are tailored to the characteristics of the school and regional characteristics. Habituation activities that can improve student character are also made mandatory programs at school. Novelty: The novelty of this research is the addition of the Tahfidz Al Qur'an program that is included in the structure of the division of class hours. This becomes a subject and extracurricular program that must be followed by Muslim students. This is a differentiator from public junior high schools in Lamongan Regency.